Application of response surface methodology for the optimization of hexavalent chromium removal using a new low-cost adsorbent - ., Ezerie Henry Ezechi, Shamsul Rahman bin Mohamed Kutty, Mohamed H (2016)
The adsorption capacity of a novel adsorbent (Ageratum conyzoide leaf powder) was investigated for Cr(VI) removal from aqueous solution. Experiments were designed with the Box–Behnken model of the response surface methodology (RSM). Preliminary experiments were conducted to obtain the optimum range of process variables used for the Box–Behnken model. Three independent variables (pH, initial concentration, and adsorbent mass) were examined. The results show that Cr(VI) removal was more favorable at pH 2. Increase in pH above 2 resulted in negative Cr(VI) removal. Cr(VI) removal increased when adsorbent mass was increased, but decreased with increase in initial concentration. Cr(VI) removal of 92% was obtained at pH 2 and adsorbent mass of 0.3 g. Experiments were successfully optimized by RSM. Kinetics study correlated with the pseudo-second-order kinetic model, whereas equilibrium study was best described by the Langmuir isotherm model with maximum adsorption capacity of 437 mg/g. Thermodynamic parameters indicate a spontaneous, exothermic, and physiosorption process